(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The note critically addresses the Constitutional Court’s ruling no. 84/2016, highlighting that the final rejection (inadmissibility) of the constitutional issue con-cerning the section of Law no. 40/2004 that bans the use of cryopreserved embryos for research purposes, eventually is based on the lack of consensus among scholars, especially scientists. But, if it is so, this solution should then prevail in every bio-law case. The Court expressly invokes Legislator’s action as the most appropriate for re-versing that legal prohibition, but at the same time it offers some hints about the po-tential contents of future legislation. In the Court’s view, the Constitution should re-main silent until the Science speaks (but there is no single “voice” in scientific debates); in the meantime, only the Legislator could rule on the issue at stake. The author nonetheless observes that, pending the law-making process, judges could supply as well. In a subsidiary logic, they could hand in to scientists the unusable embryos for research purposes, mostly considering that these would be finally wasted.